Analisis Faktor Penyebab Financial Distress pada PT Garuda Indonesia (Persero) TBK - Vena Purnamasari; Tjan, Delfina Lalita Kusuma (Jurnal Ecodemica : Jurnal Ekonomi Manajemen dan Bisnis, 2023)
Bankcruptcy is a problem that is often faced by companies, included Garuda Indonesia. Garuda Indonesia is a big transportation company. However, its financial situation is not as good as it seems. Based on the data collected, Garuda Indonesia has some problems related to liquidity, leverage, and profitability. If the company doesn’t realize its problems, the situation will only get worse. Therefore, the research goal is to find out the impact of liquidity, leverage, and profitability on Garuda Indonesia’s (GIAA) financial distress, with the expectation that the company can take a serious step to fix its financial situation. The study uses quantitative methods using the secondary data. The sample of the research are GIAA’s quarterly financial report from first quarter of 2012-fourth quarter of 2019 and uses purposive judgement sampling as a sampling method. The research shows that GIAA’s financial distress influenced by liquidity, while profitability and leverage has nonsignificant effect on financial distress. The implication of this research is that the company now must manage its assets, in form of airplanes, because those assets can cause bigger cost to be borne if the company cannot manage them wisely.Keyword: Financial distress, Garuda Indonesia, Liquidity, Leverage Profitability